Hemostasis-altering Drugs and Central Neural Block: A Survey of Anesthetic Practice in Scotland and the United Kingdom. Issue 6 (November 1996) - Millar, F. A.; Mackenzie, A.; Hutchison, G.; Bannister, J.
Abstract : Background and Objectives: There is debate regarding the use of central neural block in the presence of hemostasis-altering drugs. This study aims to examine current practice. Methods: A survey was made of the members of the Scottish Society of Anaesthetists and the U.K. branch of the European Society of Regional Anaesthesia to determine the pattern of use of central neural block in patients who are receiving drugs known to alter hemostasis. Results: Spinal anesthetics were considered safer than single epidural injections ( P < .05) and single epidural injections safer than infusions via epidural catheters ( P < .05). Conclusions: There is general agreement regarding contraindication of central neural block in the presence of full anticoagulation with either heparin or warfarin, but there is less consensus about the use of central neural block in the presence of low-dose subcutaneous heparin. There is some confusion about the role of aspirin and its duration of action.